The impact of carbon emissions trading on green total factor productivity based on evidence from a quasi-natural experiment - Haisheng Hu (Scientific Reports)
Abstract Based on a balanced panel dataset of 272 prefecture-level cities from 2000 to 2022, this paper systematically investigates the impact of the carbon emissions trading system on green total factor productivity and its underlying mechanisms from an integrated perspective of overall, dynamic, and spatial dimensions. The findings reveal that (1) the carbon emissions trading system significantly enhances regional total factor productivity, primarily by optimizing resource allocation efficiency and strengthening regional competitiveness. (2) From a dynamic perspective, the policy effect exhibited a U-shaped relationship: from 2013 to 2018, green total factor productivity was suppressed due to underdeveloped market mechanisms and the policy environment; after 2018, with market maturation and policy stabilization, the policy effects improved significantly. (3) Spatial effect analysis indicates that the emissions trading system positively influences pilot regions but generates a siphon effect on nonpilot regions, leading to regional performance divergence, although the overall impact remains positive. (4) Heterogeneity analysis reveals that the policy has more pronounced effects in regions with higher carbon intensity, stricter environmental regulations, better infrastructure, and richer resource endowments, reflecting significant regional disparities in policy effectiveness. This study provides empirical evidence and theoretical insights to optimize carbon trading policies and achieve regional green development.